Criminal Law Reform For Whistleblower Protection In Corruption Cases In Indonesia - Santy (Faculty of Law, Universitas Pekalongan, 2025)
Corruption crimes are highly detrimental to the state’s finances, national economy, and hinder growth and the continuity of national development, even violating the social and economic rights of society at large. The conventional approach to eradicating corruption is deemed ineffective and inefficient in addressing the rampant nature of this crime. This is because corruption crimes have increased over time. In this context, whistleblowers play a critical role in assisting law enforcement in exposing existing corruption. However, the significant risks faced by whistleblowers require clear and definitive legal protection. This research focuses on analyzing the policies and status of whistleblowers in corruption crimes in Indonesia and the extent to which legal protection is provided to whistleblowers. This research employs a normative legal research method with a legislative approach and a conceptual approach. The research findings show that although whistleblowers play a strategically important role in exposing corruption, their existence needs to be strongly protected by the law. The presence of whistleblowers may jeopardize their own safety and that of their families if there is inadequate protection. Therefore, strengthening the protection of whistleblowers is a strategic step to empower them as a tool to break the chain of corruption